PENTINGNYA AJARAN AGAMA KRISTEN DALAM FASE PERKEMBANGAN PSIKOLOGI ANAK USIA 8-9 TAHUN - Dendeng, Leonardo Caesar; Mongkau, Teresa Ananda Kristina; Taruh, Sannya Sari; Lumiwu, Joshua Juan (PADAMARA: Jurnal Psikologi dan Sosial Budaya, 2024)
This article examines the importance of Christian religious teachings in the psychological development of 8-9 year old children using a literature review method. Through literature analysis, it is found that Christian teachings play a significant role in the cognitive, emotional, moral, and social development of children. Christian values such as love, honesty, and forgiveness help children understand concepts of right and wrong, as well as develop empathy and critical thinking skills. Religious activities also contribute to mental health and strong self-identity. Furthermore, social interactions within the church community support the development of social skills and children’s sense of competence. In conclusion, Christian religious teachings provide a strong foundation for the holistic development of children, shaping positive character traits and supporting their success in social and academic life.